LIVING IN A LONG-TERM CARE FACILITY: DOES INSTITUTIONALIZATION REDEFINE QUALITY OF LIFE IN OLD AGE? - Guimarães, Bruna Sthefani Santos; de Almeida, Caroline Fofano; de Moura, Elton Silva; Duarte, Gabriela Cristina; Zanetti, Isabela Braga; dos Santos, Teodora Xavier; Ricardo, Thiago Corrêa de Sá; de Sousa, Rosa Gouvêa (Seven Editora, 2026)
Considering the rapid aging of the population in Brazil and the consequent increase in institutionalization in Long-Term Care Facilities for the Elderly, a phenomenon driven by complex family and social dynamics, a complex picture emerges regarding the positive and negative impacts of this process on the quality of life of the elderly population. The objective of this study is to understand how institutionalization affects the quality of life of elderly people, analyzing the factors that lead to this condition and the role played by institutions in the lives of their residents. In this context, a qualitative study was conducted, using semi-structured interviews with four elderly people, a psychologist, and a nurse, whose data were submitted to content analysis. Thus, it was observed that the experience of institutionalization is multifaceted, with adaptation being influenced by a safe physical environment and a relational dimension based on humanized care; family ties are decisive for well-being; and the feeling of belonging is subjective, oscillating between acceptance and resistance. According to that, it is possible to conclude that institutionalization can act both as a protective factor, offering support and security, and as a risk factor, presenting challenges such as depression and family distancing, with the quality of care offered being a fundamental element for promoting well-being and dignity in old age.